Linguistic means to expose the human rights aspect of citizens’ surveillance - Danilova, Elena S.; Pupynina, Elena V.; Drygina, Yulia A.; Pugach, Vladimir S.; Markelova, Oxana V. (Linguistics and Culture Review, 2021)
The paper focuses on English lexemes used in mass media publications about a new security development. The use of artificial intelligence for facial recognition and enhanced surveillance of citizens pose several ethical issues discussed in major broadsheet newspapers. Studies into the evaluation as a cognitive category have been used as the theoretical basis of the research. The contexts revealed lexical units displaying evaluation of surveillance and human rights issues. The lexemes fall within three semantic groups. Negative connotations are connected with personal experience or associations, as well as with human rights breaches, while advantages tend to be described with verbs denoting purpose. The use of AI is a highly controversial issue that deserves cross-disciplinary consideration.